RELEVANCE OF SOCIAL CONDITIONS BETWEEN FRENCH REVOLUTION AND CHARLES DICKENS’S NOVEL A Tale of Two Cities - Khoirunnisak, Tiarani; Adha, Zakiyah Apriliana; Hirda, Meilita Ivana; Santoso, Heri Dwi (Universitas Muhammadiyah Semarang, 2018)
A breath of a literary work is always related to the psycological and sociological conditions of society’s life in an era where the literary works were created. The existence of certain conditions that affect a literary work, it makes literature in the form of prose, poetry and drama can be studied with various approaches. In general, the study of a literary work is often done with two very popular approaches, namely psychological approach and sociological approach. The linkage of literary works as a reflection of a social life proves that a literary work always has partiality. Thus it can be said that literary work is a tendentious work which means having certain purposes behind its creation. This study analyzes the relevance of social conditions in the novel A Tale of Two Citieswhich is then associated with the history of the French revolution. This research uses the approach of literary sociology by focusing on historical theory and theory about social conflict. The data were collected by usingtaking note and close reading. This research shows that there are many similar social conditions between Charles Dickens's A Tale of Two Cities and the history of the French revolution. The similarities of social conditions occurred in the pre-revolutionary, revolutionary and post-revolutionary periods. Keywords: Sociological Approach, Literary Work, Social Coflict, Relevance, French Revolution